PENGARUH METODE LATIHAN SMALL SIDE GAMES DAN LATIHAN RONDO TERHADAP AKURASI PASSING PADA EKSTRAKULIKULER FUTSAL MTSN 2 TAPIN - M. Ridha Ansyari; Ramadhan Arifin; M. Mulhim (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
The purpose of this study was to find out how small side games and rondo exercises affect the passing accuracy of MTSN 2 Tapin futsal extracurricular players. The research scheme used in this study is